2014
DOI: 10.1902/cap.2013.120091
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐Implant Cystic Lesion With Unusual Cellular Changes: A Case Report

Abstract: Introduction: This report describes the history and management of a cyst developing in anatomic contact with an immediately placed dental implant. Case Presentation: The lesion presented clinically as a facial swelling of the gingiva adjacent to an osseointegrated and restored maxillary right lateral incisor implant. Radiographs showed a well‐circumscribed radiolucency, which was contiguous with the implant surface. After reflection of a mucoperiosteal flap, the lesion was enucleated in toto, and the defect wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…This lack of information may contribute to a limited understanding of peri‐implant diseases among clinicians and researchers. Through Web of Science, Embase, Pubmed, CNKI, and Wanfang database, the literature on “peri‐implant cysts” was searched since 2000, and we found that the related literature was extremely sparse 2,14–26 . All 13 retrieved articles were case reports, and together they included 16 cases with a total of 20 dental implants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This lack of information may contribute to a limited understanding of peri‐implant diseases among clinicians and researchers. Through Web of Science, Embase, Pubmed, CNKI, and Wanfang database, the literature on “peri‐implant cysts” was searched since 2000, and we found that the related literature was extremely sparse 2,14–26 . All 13 retrieved articles were case reports, and together they included 16 cases with a total of 20 dental implants.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the origins of peri‐implant cysts, studies have found that peri‐implant cysts can result from pulpal necrosis of adjacent teeth, 23,25,26 dental implant inflammation, 2,14,15 and maxillary sinus mucosa and epithelial surplus 16,18,20–22,24 . In terms of clinical manifestations, among the 13 reports found in the literature, the clinical symptoms of peri‐implant cysts included mucosal swelling, 15,16,21,23,25 pain, 15,20 fistula 25 in the local mucosa of the implant periapical area, implant mobility, 22,26 and restoration mobility, 19 while some cases had no clinical symptoms 2,14,18,24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has long been recognized that OCs frequently show the divergent differentiation and the various forms of metaplasia or prosoplasia [2][3][4]. A complex combination of two or more architectural or cellular peculiarities within one cyst suggests that with a subsequent interval of dormancy, the postembryonic odontogenic epithelium can proliferate at any time to form ameloblastic [20,21], squamous, keratotic, ghost, ciliated/mucous and sebaceous cells in pathologic states [2][3][4]. In purely pragmatic terms, the existence of "composite" OCs underscores the limitations of diagnosis based on small (marsupialized) biopsies.…”
mentioning
confidence: 99%